2008
DOI: 10.1055/s-2008-1064987
|View full text |Cite
|
Sign up to set email alerts
|

Die Bogenmacherkrankheit: Eine Berufskrankheit in der Streichbogenfabrikation

Abstract: Inhalation of wood dust from the tropical tree Fernambouc (Caesalpinia echinata) in the manufacture of string bows can cause characteristic symptoms (bow-makers disease). To confirm this observation, 177 bow-makers, working in a village near Erlangen (Bavaria), the centre of this manufacture, filled in questionnaires. Of these 36 worked with Fernambouc, 141 with other types of wood. Twelve out of these 36 suffered from dyspnoea, cough, sneezing impulses, tearing and coryza, which would disappear quickly at wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…OA, ORWilhelmsson 1984 [104] Ahman 1996 [3] Ahman 1996 [4]Cabreuva Myrpcarüis fastogoatris OA,OR, EAAPala 2010 [79] Baur 2000 [12] Innocenti 1991 [53]Cedar of Lebanon Cedra libani RSGreenberg 1972 [43]Cedar eastern white Thuja occidentalis OACartier 1986 [21] Malo 1994 [69]Cedar western red Thuja plicata OAChan-Yeung 1992 [26] Lam 1983 [67] Côté 1990 [30] Pickering 1972 [81]Cedrorana Cedrelinga catenaeformis Ducke OA, OREire 2006 [35]Cherry Prunus avium AllergyAbendroth 1992 [1] Kersten 1994 [61] Obata 2000 [75]Cocobolla / Palisander Dalbergia retusa Dalbergia spec. RS OAEaton 1973 [34] Godnic-Cvar 1990 [42]Falcata wood Albizia falcataria OATomioka 2006 [97]Fernanbouc Caesalpinia echinata RSHausen 1990 [45]Fir Abies spec. OAKespohl 2011 [62] Kersten 1994 [61]Gaboon Aucoumea spec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA, ORWilhelmsson 1984 [104] Ahman 1996 [3] Ahman 1996 [4]Cabreuva Myrpcarüis fastogoatris OA,OR, EAAPala 2010 [79] Baur 2000 [12] Innocenti 1991 [53]Cedar of Lebanon Cedra libani RSGreenberg 1972 [43]Cedar eastern white Thuja occidentalis OACartier 1986 [21] Malo 1994 [69]Cedar western red Thuja plicata OAChan-Yeung 1992 [26] Lam 1983 [67] Côté 1990 [30] Pickering 1972 [81]Cedrorana Cedrelinga catenaeformis Ducke OA, OREire 2006 [35]Cherry Prunus avium AllergyAbendroth 1992 [1] Kersten 1994 [61] Obata 2000 [75]Cocobolla / Palisander Dalbergia retusa Dalbergia spec. RS OAEaton 1973 [34] Godnic-Cvar 1990 [42]Falcata wood Albizia falcataria OATomioka 2006 [97]Fernanbouc Caesalpinia echinata RSHausen 1990 [45]Fir Abies spec. OAKespohl 2011 [62] Kersten 1994 [61]Gaboon Aucoumea spec.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 5% are numerous others high and low molecular weight organic and inorganic compounds, including proteins, which can be extracted (“wood extractives”). Examples for low molecular compounds are terpenes, terpene derivates like abietic acid, phenolic compounds, tannins, stilbenes, flavonoids, and glycosides, many with known sensitising and irritative properties [45, 107]. Specific IgE reactivity demonstrated by immunoblots with sIgE binding to single proteins from e.g. pine [95] and locust wood dust [63] have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenes and their derivatives, such as abietic acid, are characteristic of conifers (Schlünssen et al, 2012), while they are rarely found in hardwoods. Phenolic compounds, including tannins, stilbenes, and flavonoids, are concentrated in the heartwood of certain species and many of them have known sensitizing and irritative properties (Hausen et al, 1990;Woods and Calnan, 1976). Quercus species contain large quantities of tannins, while Pinus brutia contains phenolic compounds mainly in the bark (Philippou, 2014).…”
Section: Introductionmentioning
confidence: 99%